Surface modification of Ti3C2-MXene with polydopamine and amino silane for high performance nitrile butadiene rubber composites. (November 2021) - Qu, Chunhui; Li, Song; Zhang, Yaoming; Wang, Tingmei; Wang, Qihua; Chen, Shoubing
Abstract: Nitrile butadiene rubber (NBR) composites possess remarkable wear-resistance and prominent damping properties enhanced by surface modified Ti3 C2 -MXene with polydopamine and amino silane, which are prepared through solution blending and hot pressing method. The characterization results show that surface modification of Ti3 C2 -MXene improves the hardness, damping and tribological properties of unfilled NBR. In the meantime, the result also reviews that there are a lot of amino and hydroxyl groups on the surface of MXene after grafting polydopamine and amino silane. This surface modification is of benefit to muscle interfacial strength of MXene with NBR and further boosts the tribological and damping properties of NBR composites. This work explores the potentials of MXene in the friction and damping field and provides guidance for preparing highly wear-resistant and damped NBR composites. Highlights: Surface modified Ti3 C2 -MXene with polydopamine and amino silane was prepared. Nitrile Butadiene Rubber (NBR) composites with remarkable wear-resistance and prominent damping properties were obtained. The max tanδ value of modified NBR composite is about 1.0 and it's the effect damping temperature range achieves to approximately 40 °C. The wear rate of modified NBR composites has a biggest decline of 76% compared to unfilled NBR.